Impactos da logística sobre o fluxo de comércio internacional: uma abordagem do modelo gravitacional para o Brasil e seus principais parceiros comerciais - Cipolla, Caroline (2013)
In recent years, international trade has intensified and liberalized, so that decreases in border costs have become increasingly relevant. Much of these costs are associated with the excessive number of documents required to export or import, the bad infrastructure of ports and airports, among others. It is in this sense that stands out the importance of trade facilitation, principally regarding logistical factors. The trade facilitation began to be discussed at the WTO in 1996, but only in 2004 began the negotiations about it. Several papers have been written for several countries in order to assess the impact of trade facilitation on trade flows. However, studies for the brazilian case are still few, especially those that take into account logistical variables. This study aimed to identify the effects of trade facilitation, especially concerning logistics, upon the pattern of trade that includes Brazil and its major trading partners witch belong to the most important economic blocs. The data extends from 2008 to 2011 and takes into account variables on the quality of transport infrastructure and customs procedure. Gravity models considering Brazil and other 47 counties, witch were responsible for about 78% of brazilian exports in 2011, were estimated. The results evidenced the largest impact of custom variables on trade flows between countries. When considering separate models for blocs of developed and developing countries, the results showed the importance of improvements in terms of documentation, time and cost for blocs of developing countries, as well as improvement regarding the time for blocs of developed countries. With regard to transport infrastructure, good quality of rail was important for both groups. Finally, it was concluded that, for blocs of developing countries, there is a dependency on reforms in trade partners, while in blocs of developed countries the reforms made by the countries themselves have greater impact on trade flows.